Regulators of central and peripheral insulin sensitivity in humans - Latva-Rasku, Aino (fi=Turun yliopisto|en=University of Turku|, 2020)
Insulin, secreted by pancreatic β-cells, has a preeminent role in regulating metabolism in virtually all tissues. Highly conserved through evolution, intracellular insulin signaling pathways are tightly regulated, but have been recently challenged by drastic changes in our lifestyles. The following impairment in insulin response, termed insulin resistance, is an important feature of type 2 diabetes, a condition that has reached the proportions of a worldwide epidemic. It is therefore important to gain a better understanding of how insulin resistance develops, what the interplay is between different tissues, and whether pharmacologically enhancing insulin sensitivity is possible. This thesis focuses on gathering novel information about how an inherited failure in insulin signaling (Study I), brain insulin signaling (Study II), and antidiabetic medicine dapagliflozin (Study III) can alter whole-body and tissue-specific insulin sensitivity. The studies were performed by using positron emission tomography (PET) scans with a glucose analogue tracer ([18F]-FDG) together with systemic (Studies I and III) and central hyperinsulinemia (Study II) to assess changes in tissue insulin-stimulated glucose uptake (GU). The results from Study I revealed that inherited impairment in skeletal muscle insulin sensitivity resulted in insulin resistance in all key metabolic organs even before the onset of T2D, while also establishing the role of [18F]-FDG-PET in determining the phenotype associated with a rare genetic variant. In Study II, it was demonstrated that brain insulin signaling induced by intranasal insulin does not have a significant effect on GU in peripheral tissues, but results in lower brain GU under mild systemic hyperinsulinemia. While dapagliflozin did not improve insulin sensitivity either (Study III), 8 weeks of treatment reduced liver fat content, as well as subcutaneous and visceral adipose tissue mass, in overweight T2D subjects. In conclusion, these studies elucidate how a genetic variant primarily impairing skeletal muscle insulin sensitivity, central response to hyperinsulinemia, and treatment with dapagliflozin can affect tissue-specific insulin sensitivity.

Haiman β-solujen erittämällä insuliinilla on merkittävä rooli aineenvaihdunnan säätelijänä lähes kaikissa kudoksissa. Solunsisäinen insuliinisignalointi on kehittynyt evoluutiossa varhain ja on tiukasti säädeltyä, eikä ole vielä onnistunut vastaamaan erittäin nopeaan muutokseen elämäntyylissämme. Tästä seuraava kudosten heikentynyt kyky reagoida insuliiniin, eli insuliiniresistenssi, voi johtaa tyypin 2 diabeteksen puhkeamiseen. Sen vuoksi on tärkeää ymmärtää paremmin miten insuliiniresistenssi syntyy, miten eri kudokset vaikuttavat siihen, ja voidaanko tilannetta parantaa lääkkeellisesti. Tämän väitöskirjan tavoitteena on tutkia miten perinnöllinen vika erityisesti lihaksen insuliinisignaloinnissa (osatyö I), keskushermoston säätely (osatyö II) ja diabeteslääke dapagliflotsiini (osatyö III) voivat vaikuttaa kudosten insuliiniherkkyyteen. Tutkimuksissa käytettiin positroniemissiotomorafia (PET) –kuvauksia yhdessä glukoosimerkkiaineen ([18F]-FDG) kanssa. Insuliiniherkkyyden mittaamiseksi kuvausten aikana tutkittaville annettiin insuliinia verenkiertoon (osatyöt I ja III) tai nenäsumutteena (osatyö II). Osatyössä I todettiin ensisijaisesti lihaksen insuliiniherkkyyttä alentavan geenivariantin aiheuttavan insuliiniresistenssiä laajasti myös muissa kudoksissa. Lisäksi tutkimuksella vahvistettiin [18F]-FDG-PET:n roolia harvinaisten geenivarianttien vaikutusten tutkimisessa. Osatyössä II todettiin, ettei nenä-sumutteena annettu insuliini saanut aikaan merkittävää muutosta muiden kudosten glukoosiaineenvaihdunnassa, mutta aivojen glukoosinotto väheni merkittävästi sumutteen jälkeen. Myöskään dapagliflotsiini ei vaikuttanut merkitsevästi kudosten insuliiniherkkyyteen (osatyö III), mutta 8 viikon hoito vähensi maksan ja vartalon rasvan määrää ylipainoisilla tyypin 2 diabetesta sairastavilla tutkittavilla. Yhdessä nämä tutkimukset tuovat uutta tietoa siitä, miten lihaksen insuliini-resistenssiä aiheuttava geenivariantti, aivojen vaste korkeaan insuliiniannokseen, sekä hoito dapagliflotsiinilla voivat vaikuttaa kudosten insuliiniherkkyyteen